Effectiveness and Safety of Four Aerobic Exercise Intensity Prescription Techniques in Rehabilitation Training for Patients with Coronary Heart Disease - Tao Chen; Huiying Zhu; Qingyuan Su (Cardiology Research and Practice)
Background and Objectives. Exercise intensity is a key indicator for the safety and effectiveness of aerobic exercise program in cardiac rehabilitation (CR) in patients with coronary heart disease (CHD). The majority of CR guidelines recommend aerobic exercise prescription based on moderate intensity and suggest many techniques for setting the heart rate target of exercise to match the intensity. But even high-risk CHD patients rarely adhere to exercise training under medical monitoring. The effectiveness and safety of exercise under these high-intensity techniques is still a paucity of evidence. The purpose of this study was to determine if these techniques can safely and effectively inform exercise prescription for individuals with CHD. Methods. A retrospective study was conducted on all patients with CHD who were admitted to CR and completed cardiopulmonary exercise tests (CPET) in Guangdong Hospital of traditional Chinese medicine. According to the risk stratification method of CHD, all participants were divided into three groups: low, moderate, and high risk. The training target heart rates (HRt) of each participant were calculated according to the formula of heart-rate-reserve (HRR), maximum-heart-rate (MHR), target-heart-rate (THR), and anaerobic threshold (AT) method provided in the guideline. Among them, the HRR method using the maximum-heart-rate obtained by the age formula was named “HRR method A,” and that using the actual measured peak heart rate was named “HRR method B.” For the three groups, the effectiveness and safety indexes at the target-heart-rate zone set by the different formulas above are counted and compared using CPET data. Results. A total of 324 patients were included in the analysis. There was no significant difference between the target-heart-rate set by the HRR method A and AT method among the three groups (P>0.05). The mean value of HRt set by other methods was lower than the AT heart rate (P<0.05). The HRt set by the THR method was close to the AT, while that set by the MHR method was the lowest. The frequency of patients whose HRt was set by the MHR method was lower than the AT one, which was the highest. None of the participants had serious adverse events. There were no risks of ECG abnormalities in the low- and moderate-risk groups. The HRR method A had the highest incidence of various risks of ECG abnormalities, while the MHR method had the lowest one, and the safety of the THR method is close to that of the AT method (P<0.05). Conclusion. The heart rate calculated by HRR method A is more consistent with the actual AT. All four techniques are safe in low- and moderate-risk patients. In high-risk patients, using HRR method A has certain risks. It is recommended to use the MHR method for safety reasons, but its effectiveness is low. If considering both effectiveness and safety, the THR method can be conservatively selected at the beginning of the CR program.